Painful Complications After Cosmetic Surgery: Management of Peripheral Nerve Injury. (22nd October 2018) - Chopra, Karan; Kokosis, Georgios; Slavin, Benjamin; Williams, Eric; Dellon, A Lee
Abstract: Background: Aesthetic procedures are among the most common surgeries performed by plastic surgeons. The prevalence of persistent pain remains unknown and underappreciated in the plastic surgery literature. Objectives: The purpose of this article was to increase awareness of this problem while describing the diagnostic and management strategies for patients with postoperative pain after aesthetic plastic surgery. Methods: A literature review was performed utilizing the PubMed database to identify painful complications of brachioplasty, blepharoplasty, rhytidectomy, abdominoplasty, breast augmentation, mastopexy, and breast reduction. A treatment algorithm was described to guide plastic surgeons presented with patients reporting pain after aesthetic surgery. Results: Title and abstract review followed by application of inclusion and exclusion criteria resulted in 20 clinical studies for this review, including lateral femoral cutaneous nerve, iliohypogastric nerve, and intercostal nerves after abdominoplasty; median antebrachial cutaneous nerve after brachioplasty; supraorbital, supratrochlear, and infratrochlear nerves after blepharoplasty; greater auricular nerve, auriculotemporal nerve, and zygomaticofacial nerve after rhytidectomy; and intercostobrachial nerve after breast surgery. Conclusions: Neuromas can be the source of pain following aesthetic surgery. The same clinical and diagnostic approach used for upper and lower extremity neuroma pain can be employed in patients with persistent pain after aesthetic surgery. Level of Evidence: 4: